ANALYSIS OF FACTORS INFLUENCING INCOME OF OUTBOARD MOTOR FISHERMAN BOATS IN PANDAN DISTRICT TAPANULI CENTRAL DISTRICT - Sonia Muslimah Sinaga; Adhiana Adhiana; Riani Riani (LPPM Universitas Malikussaleh - Indonesia, 2023)
This research was conducted in Pandan District, Tapanuli Tengah Regency from October to November 2022. This research was conducted because there was a significant difference in income between outboard motor fishermen in Muara Nibung Village and outboard motor fishermen in other sub-districts in Pandan District. Fishermen in Kelurahan Muara Nibung have the lowest income among the 22 villages/kelurahan in Pandan Subdistrict, even though the kelurahan has fishery potential that is not inferior to other kelurahan/villages. This difference of opinion can be caused by factors that influence opinion such as experience, distance traveled, length of time at sea and operational costs used by fishermen in fishing activities. This study aims to analyze the influence of experience, distance traveled, length of time at sea and operational costs on fishermen's income in Pandan District, Tapanuli Tengah Regency. The data analysis method used is Multiple Linear Regression. The results showed that the coefficient of determination (Adjust R2) was 0.929 or 92.9%. The percentage influence of experience, distance traveled, and length of time at sea is able to explain income by 92.9%, the remaining 7.1% is explained by other variables outside the model. The results of the F test simultaneously experience, mileage, and length of time at sea have a significant effect on fishermen's income. The results of the partial t test show that experience, distance traveled, and length of time at sea have a significant positive effect on the income of fishermen in Pandan District, Tapanuli Tengah Regency. Keywords: Income, Outboard Motor Boat Fisherman, Multiple Linear Regression